2014
DOI: 10.7554/elife.05105
|View full text |Cite
|
Sign up to set email alerts
|

A highly tunable dopaminergic oscillator generates ultradian rhythms of behavioral arousal

Abstract: Ultradian (∼4 hr) rhythms in locomotor activity that do not depend on the master circadian pacemaker in the suprachiasmatic nucleus have been observed across mammalian species, however, the underlying mechanisms driving these rhythms are unknown. We show that disruption of the dopamine transporter gene lengthens the period of ultradian locomotor rhythms in mice. Period lengthening also results from chemogenetic activation of midbrain dopamine neurons and psychostimulant treatment, while the antipsychotic halop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
195
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(208 citation statements)
references
References 83 publications
12
195
1
Order By: Relevance
“…Alternatively, this could be related to the decrease in DA, observed only for LO fish. Indeed it has recently been shown that a decrease in DA in mouse brain led to a shortening of ultradian activity period (higher fractionation of activity, [44]). Our results are also in agreement with behavioural changes observed in adult zebrafish after seven months of exposure to low BaP concentrations (waterborne exposure; effects seen starting at 0.05–0.5 nM (12.6–126 ng·L −1 )).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, this could be related to the decrease in DA, observed only for LO fish. Indeed it has recently been shown that a decrease in DA in mouse brain led to a shortening of ultradian activity period (higher fractionation of activity, [44]). Our results are also in agreement with behavioural changes observed in adult zebrafish after seven months of exposure to low BaP concentrations (waterborne exposure; effects seen starting at 0.05–0.5 nM (12.6–126 ng·L −1 )).…”
Section: Resultsmentioning
confidence: 99%
“…Independent of the SCN and of circadian clock function, chronic methamphetamine administration induces activity rhythms with a period close to 24 h (Mohawk et al, 2009;Tataroglu et al, 2006). A recent study from Blum and colleagues indicates that the MASCO is a manifestation of a newly discovered dopaminergic oscillator (Blum et al, 2014). They have shown that in the absence of a functional molecular circadian clock, hyperdopaminergic DAT À/ À mice have longer period ultradian rhythms, and increasing DA signaling can even evoke behavioral rhythms with periods up to 24 h and longer.…”
Section: Discussionmentioning
confidence: 99%
“…Of note is that this seasonally responsive central thermostat governs the sensitivity of certain brain dopamine-2 (D 2 ) receptors [74], which are the therapeutic mood-stabilizing neuroreceptor targets for the atypical antipsychotic medications that are effective for mixed depressive states [17]. Further, genetic variations affecting central D 2 receptor function regulate variations in habitual sleep duration in humans [75], while striatal extracellular dopamine concentrations and striatal D 2 receptors modulate the activity-rest ratio in mice [76]. Thus, studies of the thermostat’s regulation of central D 2 receptors, dopamine, mood, arousal, and E-M and sleep duration in spring mixed depressive states become of interest [77].…”
Section: Discussionmentioning
confidence: 99%